(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Hanum AF, Azzahra Y, Nursafithri ZA, Dores SD, Natasya AM, Iskandar J, Saensouk S, Setyawan AD. 2025. Local perception of traditional foods in Wonosobo Traditional Markets, Central Java, Indonesia. Asian J Ethnobiol 8: 49-55. Traditional markets are an important part of Indonesian culture due to their capacity to negotiate prices and provide affordable, everyday essentials as well as distinctive gastronomic experiences. Wonosobo has a rich culinary heritage that promotes both local culture and tourism, and it is well-known for its variety of traditional delicacies. This study aims to understand the Wonosobo people’s perceptions of traditional food and its comparison with modernized food. This study focuses on the Kertek and Wonosobo Main Markets in Wonosobo District, Central Java, to investigate consumer preferences and perceptions of traditional food. In October 2024, 90 respondents, 46 women and 44 men, were interviewed as part of the data-gathering process. Results show that 68.4% of respondents strongly prefer traditional foods, valuing them for their health benefits and cultural significance. A smaller percentage (3.8%) noted that modernized food availability impacts traditional food choices. Younger respondents tended to modern food, highlighting a generational shift. This suggests a need for strategies to preserve traditional foods while balancing them with modern culinary trends. The difference in preference for traditional food and modernized food can be influenced by globalization. Therefore, special attention is needed to traditional food so that it remains sustainable. The importance of governmental and local initiatives in promoting and sustaining traditional foods has to meet evolving consumer preferences, ensuring their relevance in a modernizing food landscape.